Management of Continuous Renal Replacement Therapy Following Coronary Artery Bypass Grafting in the Intensive Care Unit - Synthana, Meta Restu; Jufan, Akhmad Yun; Wisudarti, Calcarina Fitriani Retno (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2021)
Background: Acute kidney injury (AKI) after cardiac surgery is a serious complication with a high occurrence, leading to increased morbidity and mortality. Continuous renal replacement therapy (CRRT) is the preferred method for replacing kidney function in patients with hemodynamic instability, especially during the critical postoperative period in the intensive care unit (ICU).Case: A 76-year-old man with a history of ischemic heart disease and chronic heart failure underwent off-pump coronary artery bypass grafting (CABG). The patient had comorbidities including obesity, obstructive sleep apnea (OSA), chronic obstructive pulmonary disease (COPD), pneumonia, and chronic kidney disease (CKD). During intensive postoperative care, the patient experienced a progressive decrease in urine output, rising urea and creatinine levels, and significant fluid overload. CRRT with continuous venovenous hemodiafiltration (CVVHDF) mode was started on the first day of ICU admission, and clinical improvement was observed after four days of therapy.Discussion: Patients with multiple comorbidities often experience a deterioration in kidney function after surgery, requiring prompt intervention. The critical role of CRRT in stabilizing fluid and metabolic balance, while simultaneously maintaining hemodynamic stability, cannot be overstated. Careful monitoring of volume status, hemodynamics, and laboratory results is essential to determine the duration of therapy and evaluate its effectiveness.Conclusion: CRRT is an effective treatment for patients after CABG with AKI and hemodynamic instability. A team-based approach and proper monitoring are crucial for the success of therapy and patient recovery.